UI/UX Design Modeling on Chatting and Forum Applications Using Design Thinking - Anantya, Arya Rezza; Wijaya, Anugerah Bagus; Suliswaningsih, Suliswaningsih (Journal of Multimedia Trend and Technology, 2024)
Informatics is one of the study programs at the private university of Amikom University Purwokerto which prioritizes learning on the development of Information Technology, but the problems faced vary such as the absence of a campus facility for discussion and community, difficulty in conveying the problems they face, especially related to assignments and materials presented by lecturers. The purpose of this study is to design a visual concept of user interface design and prototype flow design for the Chatting and Forum Discussion Forum application using the Design Thinking method. The method used involves iterative steps to understand user needs, build prototypes, and test the resulting solutions. In addition, the usability testing method is used to test the prototype results of the interface that has been created, with a focus on user experience. The final result of this study is a user interface and prototyping that have passed the testing stage according to usability testing standards, task completion testing using the SEQ (Single Ease Question) method on each task has an average task completion above 6. And the results of the SUS (System Usability Scale) method have a value of 88.3 meeting the SUS acceptable scoring aspect with a grade scale B which shows that the project created is easy to use. Successfully designed a visual design concept through user interface and user experience design of online discussion forum platform media using the Design Thinking method through the stages of Empathize, Define, Ideate, Prototype, and Testing.